Insulin treatment reverses the increase in atrogin-1 expression in atrophied skeletal muscles of diabetic rats with acute joint inflammation - Pinheiro-Dardis, Clara Maria [UNESP]; Gutierres, Vânia Ortega [UNESP]; Assis, Renata Pires [UNESP]; Peviani, Sabrina Messa; Delfino, Gabriel Borges; Durigan, João Luiz Quagliotti; Salvini, Tania de Fátima; Baviera, Amanda Martins [UNESP]; Brunetti, Iguatemy Lourenço [UNESP] (Taylor & Francis, 2018)
Background: The aim of this study was to evaluate the changes in biomarkers of skeletal muscle proteolysis (atrogin-1, muscle RING finger-1 protein [MuRF-1]) and inflammation (nuclear factor kappa-B) in skeletal muscles of rats under two catabolic conditions, diabetes mellitus (DM) and acute joint inflammation, and the effects of insulin therapy. Materials and methods: Male Wistar rats were divided into groups without diabetes – normal (N), saline (NS), or ι-carrageenan (NCa) injection into the tibiotarsal joint – and groups with diabetes – diabetes (D), plus insulin (DI), saline (DS), or ι-carrageenan (DCa) injection into the tibiotarsal joint, or ι-carrageenan injection and treatment with insulin (DCaI). Three days after ι-carrageenan injection (17 days after diabetes induction), tibialis anterior (TA) and soleus (SO) skeletal muscles were used for analysis. Results: DM alone caused a significant decrease in the mass of TA and SO muscles, even with low levels of atrogenes (atrogin-1, MuRF-1), which could be interpreted as an adaptive mechanism to spare muscle proteins under this catabolic condition. The loss of muscle mass was exacerbated when ι-carrageenan was administered in the joints of diabetic rats, in association with increased expression of atrogin-1, MuRF-1, and nuclear factor kappa-B. Treatment with insulin prevented the increase in atrogin-1 (TA, SO) and the loss of muscle mass (SO) in diabetic-carrageenan rats; in comparison with TA, SO muscle was more responsive to the anabolic actions of insulin. Conclusion: Acute joint inflammation overcame the adaptive mechanism in diabetic rats to prevent excessive loss of muscle mass, worsening the catabolic state. The treatment of diabetic-carrageenan rats with insulin prevented the loss of skeletal muscle mass mainly via atrogin-1 inhibition. Under the condition of DM and inflammation, muscles with the prevalence of slow-twitch, type 1 fibers were more responsive to insulin treatment, recovering the ability to grow.
Keywords: Atrogenes; Creatine kinase; Diabetes mellitus; Inflammation; Insulin; Muscle proteolysis; NF-κB